2020
DOI: 10.1103/physrevlett.124.027802
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Roughness Speeds Up Segmental Dynamics of Thin Polymer Films

Abstract: We show that the segmental mobility of thin films of poly(4-chlorostyrene) prepared under nonequilibrium conditions gets enhanced in the proximity of rough substrates. This trend is in contrast to existing treatments of roughness which conclude it is a source of slower dynamics, and to measurements of thin films of poly(2-vinylpiridine), whose dynamics is roughness invariant. Our experimental evidence indicates the faster interfacial dynamics originate from a reduction in interfacial density, due to the noncom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 46 publications
5
31
1
Order By: Relevance
“…Samples were spin-coated at a constant spinning rate (3000 rpm). Tests on P4ClS, a polymer whose dynamics is particularly sensitive to changes in the specific volume (3,45) and preparation conditions (46)(47)(48), revealed that the spinning rate does not affect molecular dynamics.…”
Section: Dielectric Measurementsmentioning
confidence: 99%
“…Samples were spin-coated at a constant spinning rate (3000 rpm). Tests on P4ClS, a polymer whose dynamics is particularly sensitive to changes in the specific volume (3,45) and preparation conditions (46)(47)(48), revealed that the spinning rate does not affect molecular dynamics.…”
Section: Dielectric Measurementsmentioning
confidence: 99%
“…Interestingly, although these examples have demonstrated that interactions with the solid substrate are an important parameter controlling the behavior of soft materials confined at the nanoscale, this issue has been mainly explored by simple modification/functionalization of the solid substrate surface, including changes in its polarity, specific interactions (H-bonds), hydrophilicity, and hydrophobicity. ,, However, another promising strategy to modify the strength of the interfacial interactions that is less investigated in the literature is to change the surface morphology (i.e., roughness). Molecular dynamics simulation studies pointed out that variation of this parameter has a strong influence on the mobility of adsorbed molecules and the dynamics of polymer films in general. Recently, this supposition was also confirmed by experimental data showing that the segmental dynamics of polymers supported as thin layers “prepared under non-equilibrium conditions” was enhanced near the rough interface because of the perturbation of the interfacial free volume and “noncomplete filling of surface asperities” …”
mentioning
confidence: 90%
“…This trend implies the presence of a layer, whose properties differ from the bulk, extending for approximately 10−15 nm at each interface (we remind the symmetric Al/polymer/Al geometry of our samples). Among the possible candidates for the mechanisms inducing the formation of such layer with a T g larger than in bulk, we considered the following: (i) an increase in local order, 18 (ii) the formation of crystalline structures, 19 and (iii) chain immobilization 20 in the proximity of the supporting interface (Al); we discarded the effect of substrate roughness, 21 whose contribution to slower dynamics has been recently challenged by measurements in the same sample geometry, 22 and that of curvature, 23,24 as the samples considered are confined between two flat walls. The hypothesis (i) would imply a better alignment of dipole moments, yielding a large increase in intensity of the dielectric signal 25 upon thickness reduction, which is in neat disagreement with our results.…”
mentioning
confidence: 99%